FAKTOR LINGKUNGAN YANG BERHUBUNGAN DENGAN KEJADIAN LEPTOSPIROSIS DI KOTA SEMARANG - Ghinaa Maniiah; Mursid Raharjo; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Leptospirosis is one of the emerging infectious diseases caused by pathogenic bacteria called leptospira and it is transmitted from animals to humans (zoonoses). In Semarang, the death rate due to leptospirosis is higher than the national average. This study aimed to analyze the environmental factors that influence the incidence of leptospirosis in the city of Semarang. This type of research is observational case-control design. Population this study were 64 patients with leptospirosis with a sample of 31 cases and 31 controls. Descriptive results showed that the majority of respondents aged 15-49 years with the majority of the work as a trader and the average male gender. Univariate analysis showed that there is an 58.1% puddle, 83.9% bad condition of the ditch, 77.4% there where rats, 64.5% do not have a pet, 61.3% there is no activity in water, 64.5 % no history of contact with dead rats and 87.1% no history of injuries. Bivariate Analysis showed an association between the presence of stagnant water (p = 0.040), the condition of the sewers (p=0,014), presence of rats (p=0.002) and history of injuries (p=0,001). Laboratory results showed that 62 water samples examined contained 38 (61,29%) positive water samples contained bacteria Leptospira which mostly comes from the bath water sources. The conclusions of the environmental factors that influence the incidence of leptospirosis in Semarang City.